Strategy for Developing the Quality of Islamic Education Based on Digital Technology through Teacher Working Groups - Wahab, Wahab; Apjan, Syarifah Sajila; Hemafitria, Hemafitria (Fitrah: Journal of Islamic Education, 2025)
The main context of this study arises from the low quality of Islamic Religious Education learning in schools, which is caused by the suboptimal use of digital technology among teachers. Limited digital competence, a lack of innovative learning media, and weak professional collaboration have resulted in Islamic Religious Education learning that remains conventional and less responsive to students’ needs. This study aims to analyze strategies for strengthening the quality of Islamic Religious Education through digital-based initiatives facilitated by the Teacher Working Group in West Pontianak. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observations, and document analysis involving twelve informants, including Islamic Religious Education teachers, instructors, group administrators, and supervisors. The findings indicate that quality strengthening is carried out through needs-based planning, interactive digital training, continuous mentoring, and collaborative professional learning communities. The novelty of this research lies in its focus on the Teacher Working Group as a center of digital transformation for Islamic Religious Education. The implication of this study is the need to expand this strategic model to enhance digital competence among Islamic Religious Education teachers.